A Sensitive Epinephrine Sensor Based on Photochemically Synthesized Gold Nanoparticles - Metin, Eyup; Batibay, Gonul S.; Aydin, Meral; Arsu, Nergis (MDPI, 2025)
In this study, gold nanoparticles (AuNPs) and AuNPs-graphene oxide (AuNPs@GO) nanostructures were synthesized in aqueous media using an in-situ photochemical method with bis-acyl phosphine oxide (BAPO) photoinitiator as a photoreducing agent in the presence of HAuCl4. The parameters for synthesis were arranged to obtain stable and reproducible dispersions with desirable chemical and optical properties. Both AuNPs and AuNPs@GO were employed as sensing platforms for the detection of epinephrine in two concentration ranges: micromolar (mu M) and nanomolar (nM). Field emission scanning electron microscopy (FE-SEM), Dynamic Light Scattering (DLS), UV-Vis absorption, fluorescence emission, and Fourier Transform Infrared (FT-IR) spectroscopy techniques were used to investigate the morphological, optical, and chemical properties of the nanostructures as well as their sensing ability towards epinephrine. Fluorescence spectroscopy played a crucial role in demonstrating the high sensitivity and effectiveness of these systems, especially in the low concentration (nM) range, confirming their strong potential as fluorescence-based sensors. By constructing calibration curves on best linear subranges, limit of detection (LOD) and limit of quantification (LOQ) were calculated with two different approaches, SEintercept and Sy/x. Among all the investigated nanostructures, AuNPs@GO exhibited the highest sensitivity towards epinephrine. The efficiency and reproducibility of the in-situ photochemical AuNPs synthesis approach highlight its applicability in small-molecule detection and particularly in analytical and bio-sensing applications.
Keywords: photochemical synthesis; gold nanoparticles; epinephrine detection; small molecule detection; LOD; LOQ; Chemistry; Electrochemistry; Instruments & Instrumentation